Austria : Publication of Financial Sector Assessment Program Documentation-Technical Note on Macroprudential Policy Framework and Tools. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This technical note assesses strengths and weaknesses of the macroprudential policy framework in Austria and provides policy recommendations. Financial sector resilience in Austria has improved significantly since the global financial crisis, and the macroprudential policy framework has been formalized. The institutional framework is appropriate for conducting macroprudential policy effectively, but it could be strengthened in some areas. However, some structural vulnerabilities to financial stability remain and cyclical risks are on the rise. Banks' low efficiency and the resulting low profitability of domestic operations continues to be a key concern, especially given the fact that the Central Europe and South Eastern Europe region accounts for over 40 percent of Austrian banks' consolidated profits. The framework contains a clear mandate, well-defined objectives, and provides enough powers to the Financial Market Stability Board. Broad-based vulnerabilities remain contained but build-up of risks in the real estate sector warrants further action. The framework for addressing structural vulnerabilities is sophisticated, however, further improvements could be considered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet